Green matters [ green building - Drane, Margaret; Drane, Paul; Farrow, Nick; Holmes, Abe (Green and sustainable technology series, 2010)
Information technology giant,wipro, considers its software development centre India's greenest building to date. The development,spread across 1.2 acres of land, has received international recognition for its many eco-friendly features.the building is a model of energy efficiency and environmental friendliness. It takes full advantage of natural lighting, with 75% of the building day-lit, including the spacious reception area